2022
DOI: 10.1021/acs.energyfuels.1c03662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Single Coal Particle Combustion Process under O2/CO2 Atmosphere Based on Spectral Diagnostics Technology: Combination of Spectroscopic Characteristics and Flame Temperature

Abstract: This work studies the single coal particle combustion process in an O2/CO2 atmosphere based on spectral diagnostics technology in a visual drop tube furnace (VDTF). The chemiluminescence characteristics of OH*, CH*, Na*, and K* in single coal particles at two reaction stages and different oxygen fractions (X i,O2 ) are investigated. The results show that both flame temperature and alkali metal spectral intensity increase first and then decrease, and the trend of temperature variation is consistent with that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first report applying this spatial and temporal resolved method to metalorganic single droplet combustions. Studies including spatially resolved flame emission spectroscopy have been reported for particle combustion, 32,33 flame combustions 34–37 and for pyrotechnic combustion behaviour (temporal and spatial). 38…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report applying this spatial and temporal resolved method to metalorganic single droplet combustions. Studies including spatially resolved flame emission spectroscopy have been reported for particle combustion, 32,33 flame combustions 34–37 and for pyrotechnic combustion behaviour (temporal and spatial). 38…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report applying this spatial and temporal resolved method to metalorganic single droplet combustions. Studies including spatially resolved flame emission spectroscopy have been reported for particle combustion, 32,33 flame combustions [34][35][36][37] and for pyrotechnic combustion behaviour (temporal and spatial). 38 Previous studies have analysed the combustion of metalorganic precursors using high-speed imaging, revealing mass transfer and phenomenological combustion behaviours/ mechanism such as micro explosions.…”
Section: Introductionmentioning
confidence: 99%